Types and Amount of Marine Debris in the Beruk Island Rupat Utara , Bengkalis Regency, Riau Province. - Lisa Ayuningtyas Sitorus; M. Fauzi M. Fauzi2; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMarine debris was commonly flown by the current and stranded in the coast. A study aims to investigate the type and amount of marine debris in the Beruk Islandwas conducted in May 2018. A survey method was used in this study. Samplingswere done three observation stations, namely S1 (Southern area), S2 and S3 (Northernarea).Marine debris were collected from 3 plots (25x60 m) placed along the transect line. Results shown that the types of marine debris found in the observation areawere plastics, glass bottles, used tires, cans, nets and styrofoam. Total amount of marine debris in the Beruk Island areawas 87.7 kg.The most common debris found was plasticthat were categorized as makrodebris.Keywords: Marine waste, Plastic remain, Makrodebris, Plastic pollution